A Parallel new high order iterative algorithm on shared memory multiprocessors parallel computer - Mohamed Othman,; Abdul Rahman Abdullah, (Penerbit UKM, 2004)
A new fast high-order points iterative algorithm of O(h4) applied to linear systems arising from discretization of 2D Poisson problem was recently introduced by the writers. This algorithm shows drastic reduction in execution time as compared to the standard high-order points iterative algorithm. In this paper, the parallel implementation of the algorithm with optimal strategy on shared memory multiprocessors (SMP) was presented and discussed. The numerical results of the test problem are included